Cybersecurity Literacy Among Mass Media Journalists In Central Java - Setyowati, Retno Manuhoro; Safira, Citra; Pramucitra, Sinta (Jurusan Ilmu Komunikasi UTM, 2024)
Notes of the Alliance of Independent Journalists (AJI Indonesia) at the end of 2022, the number of digital attacks on journalists increased compared to 2021. There were 15 digital attacks in 2022, while in 2021, there were only 5 cases recorded. Attacks, or what is commonly referred to as digital violence, refer to the notion of violence in which the perpetrator attacks network infrastructure or uses digital technology. Meanwhile, digital attacks becoming a trend during 2022 are hacking experienced by journalists and DDoS targeted at media organization sites. However, not all mass media have prepared anticipation for the potential for digital violence, including not all journalists who understand cybersecurity's importance in carrying out their duties. This research seeks to explore the meaning of journalists related to cyber security in their journalistic work and to record real experiences of how anticipation and strategies are carried out so that they do not just become victims of cyber-attacks. The method used is qualitative with an interpretive phenomenological analysis (IPA) approach. An approach where data is obtained and studied in an in-depth way, and sees each case is something that has its characteristics. The key word of this research lies in the technique of analysis and interpretation of data that is descriptive, which is presented using a distinctive language and does not aim to generalize the results. The research location is in the city of Semarang, with data collection techniques through in-depth interviews, surveys, observations, and documentation of the research subjects, in this case, journalists from various mass media in Central Java.